Faktor Risiko Abortus: Penelitian Kasus-Kontrol Berbasis Rumah Sakit - Setiyorini, Ana; Mustika Dewi , Wulan Mei (I Care Jurnal Keperawatan STIKes Panti Rapih, 2025)
Background: The incidence of abortion is clinically stated to be around 15-20% of all pregnancies. On average, there are 114 cases of abortion every hour and can approach 50%. Factors that are thought to be associated with the incidence of abortion are fetal, maternal, and external factors. Objective: Knowing the magnitude of the risk of abortion in mothers with a previous history of abortion and other factors that affect the incidence of abortion, namely maternal age at pregnancy, parity, and pregnancy distance. Methods: Observational study with case control design at Yogyakarta Private Hospital. There were 50 cases (abortion with gestational age <20 weeks) and 100 randomly drawn controls (at term labor). Univariate, bivariate analysis with Chi Square at the level of significance p<0.05, 95% CI. Multivariate analysis of logistic regression models to estimate the odds ratio and 95% CI of the risk of history of abortion on the incidence of abortion. Results: Multivariate logistic regression analysis showed that mothers with a previous history of abortion had a lower risk of having an abortion than mothers who had never had an abortion (OR = 0.39; 95% CI: 0.17–0.90). Factors that significantly increased the risk of abortion were maternal age at pregnancy <20 or >35 years (OR = 2.69; 95% CI: 1.17-6.16), high parity (OR = 11.15; 95% CI: 1.32-93.99), and pregnancy spacing that was too close or far apart (OR = 3.30; 95% CI: 1.48-7.35). Conclusion: A history of abortion was found to be a protective factor for the incidence of abortion and requires further study to understand its mechanism. Key words: history of abortion, incidence of abortion, risk factors, case control